Die vertaling van [vreemde taal weggelaat]-uitdrukkings in die Nuwe Testament - Tolmie, D. F. (HTS teologiese studies, 2002)
The translation of [foreign font omitted]-phrases in the New Testament In most cases translators translate the [foreign font omitted] phrases in the New Testament literally. In this article such an approach is questioned, in particular when a translator wishes to translate in such a way that the meaning of the original text is transmitted accurately to the reader. In order to help translators to translate the [foreign font omitted] phrases in the New Testament in a meaningful way, the possible meaning these phrases may have is categorised as follows: [foreign font omitted] phrases in which [foreign font omitted] functions as the (direct) object of an event; [foreign font omitted] phrases in which a movement towards [foreign font omitted] can be detected; [foreign font omitted] phrases that are used instrumentally; [foreign font omitted] phrases indicating state/status; phrases that are used to indicate cause. In each case several examples are discussed.